P2‐NaCo0.5Mn0.5O2 as a Positive Electrode Material for Sodium‐Ion Batteries. Issue 16 (9th September 2015) - Yang, Peilei; Zhang, Chaoyang; Li, Malin; Yang, Xu; Wang, Chunzhong; Bie, Xiaofei; Wei, Yingjin; Chen, Gang; Du, Fei
Abstract: As a promising positive electrode material for sodium‐ion batteries (SIBs), layered sodium oxides have attracted considerable attention in recent years. In this work, stoichiometric P2‐phase NaCo0.5 Mn0.5 O2 was prepared through the conventional solid‐state reaction, and its structural and physical properties were studied in terms of XRD, XPS, and magnetic susceptibility. Furthermore, the P2‐NaCo0.5 Mn0.5 O2 electrode delivered a discharge capacity of 124.3 mA h g −1 and almost 100 % initial coulombic efficiency over the potential window of 1.5–4.15 V. It also showed good cycle stability, with a reversible capacity and capacity retention reaching approximately 85 mA h g −1 and 99 %, respectively, at the 5 C rate after 100 cycles. Additionally, cyclic voltammetry and ex situ XRD were employed to explain the electrochemical behavior at the different electrochemical stages. Owing to the applicable performances, P2‐NaCo0.5 Mn0.5 O2 can be considered as a potential positive electrode material for SIBs. Abstract : It's just a phase : Using a P2‐NaCo0.5 Mn0.5 O2 electrode as a cathode material for sodium‐ion batteries gives an initial discharge capacity of 124.3 mA h g −1 and almost 100 % coulombic efficiency at a current of 12 mA g −1 for 1.5–4.15 V. The P2‐NaCo0.5 Mn0.5 O2 electrode also shows good cycle stability and a long cycle life, indicating that it is suitable for application in sodium‐ion batteries.